The reliability of measuring severity of stuttering in a foreign language. (3rd April 2022) - Hoffman, Laura; Wilson, Linda; Hewat, Sally
ABSTRACT: Purpose: With increasingly multicultural and linguistically diverse societies, speech-language pathologists (SLPs) are being challenged with the task of working with clients who speak foreign languages. However, there is still a lack of evidence exploring how well SLPs are able to make reliable measurements of stuttering in languages other than their own. This study expands on existing knowledge and offers new reliability data for a different language that is commonly spoken worldwide, Vietnamese, enabling comparisons to be made to other foreign languages. Methods: This study was undertaken to estimate the reliability of English-speaking SLPs' use of a severity rating (SR) scale, to measure severity of stuttering in a familiar (English) and foreign (Vietnamese) language. Fifty-nine English-speaking SLPs rated 20 audio speech samples (10 English and 10 Vietnamese) of adults who stutter using a 9-point SR scale on two separate occasions. Results: Results of the present study concur with previous studies identifying that language familiarity plays a pivotal role with SLPs' abilities to reliably measure severity of stuttering. SLPs showed better agreement measuring severity of stuttering for mild and severe stuttering, regardless of familiarity with language. However, greater variability (poorer reliability) was found in the moderate range of the scale for both familiar (English) and foreign (Vietnamese) languages. Conclusion: Results highlight the need for future research to focus on finding ways to assist SLPs to improve their reliability in the middle range of the scale, and further support stuttering measurement training packages to be developed in different languages.